2006
DOI: 10.1590/s0101-20612006000400032
|View full text |Cite
|
Sign up to set email alerts
|

Teores de isoflavonas e capacidade antioxidante da soja e produtos derivados

Abstract: RESUMOO objetivo deste estudo foi determinar a capacidade antioxidante, o teor e as formas de isoflavonas presentes nos produtos derivados de soja e compará-los à soja em grão. A capacidade antioxidante foi mensurada por meio do método de cooxidação do β-caroteno/ ácido linoléico e pelo seqüestro de radicais livres (DPPH•). Os resultados mostraram que o conteúdo de isoflavonas nos produtos variou de 95 a 711 mg/100 g (b.s.) e o teor de fenólicos totais de 101 a 413 mg equivalentes de catequina/100 g (b.s.), se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 30 publications
3
3
0
4
Order By: Relevance
“…It is important to note that, in our study, this difference was statistically significant. In another study by Barbosa et al [20], the authors found 381 ± 3 mg 100 g −1 of total isoflavones in defatted soybean flour obtained from conventional commercial soybeans, which is similar to our results for conventional commercial soybean, because isoflavones were assessed on degreased samples. Duke et al [21] performed a study using a different approach to evaluate the response of transgenic cultivars DP 5806 RR and Asgrow 3701 RR subjected to different environmental conditions but similar herbicide applications.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It is important to note that, in our study, this difference was statistically significant. In another study by Barbosa et al [20], the authors found 381 ± 3 mg 100 g −1 of total isoflavones in defatted soybean flour obtained from conventional commercial soybeans, which is similar to our results for conventional commercial soybean, because isoflavones were assessed on degreased samples. Duke et al [21] performed a study using a different approach to evaluate the response of transgenic cultivars DP 5806 RR and Asgrow 3701 RR subjected to different environmental conditions but similar herbicide applications.…”
Section: Resultssupporting
confidence: 91%
“…). However, Barbosa et al [20] found different proportions of total isoflavones: 42.8 and 39.1 mg•100 g −1 of β-glycosides, 52.5 and 50.6 mg•100 g −1 of malonylglycosides, 4.0 and 7.2 mg•100 g −1 of aglycones, and 1.0 and 2.9 mg•100 g −1 of acetylglycosides in soybeans and defatted flour, respectively. However, these authors did not have information about the presence of transgenes in the tested samples.…”
Section: Resultsmentioning
confidence: 98%
“…This trend was reflected in the antioxidant activity, with the greater antioxidant capacity displayed by samples with a longer fermentation time due to an increase in the aglycone forms. These results were similar to those found by Barbosa et al (2006), who evaluated the isoflavone profile and the amount of phenolic compounds in different soybean-based products and the influence of these products on the antioxidant capacity. Their results showed that the antioxidant capacity is related not only to the amount of total phenolic compounds but also to the amount and forms of the aglycones and the types of conjugation.…”
Section: Antioxidants From Plant Sourcessupporting
confidence: 90%
“…O conteúdo total foi similar ao encontrado por Carrão-Panizzi et al (1998), em estudo realizado com variedades de soja cultivadas no Paraná, cujo teor de isoflavonas foi de 54 a 147 mg/100 g. Barbosa et al (2006 a) analisaram uma variedade de grãos de soja adquiridos no comércio de São Paulo. O teor de isoflavonas foi de 110 ± 2 mg/100 g, resultado similar ao encontrado em outros trabalhos.…”
Section: Agliconasunclassified